Design of 433 MHz Communication Protocol and Implementation of Gateway in Intelligence Home - Yang Ge; Dagang Li (Dianxin kexue)
According to the network establishing demands of the internal network of intelligent home, such as low cost, low data rate, short distance communication, a type of 433 MHz RF communication protocol stack based on CC1101 was created and a gateway based upon the embedded operating system called μC/OS-II and micro controller called STM32F407 was implemented. This intelligent gateway equipped with Wi-Fi, GSM, ethernet and other functional modules works with the 433 MHz RF communication protocol stack to achieve multiple intelligent controls. Specifically the following points were mainly presented: the design of 433 MHz RF protocol stack, the definition of communication protocol and node model, the establishment of 433 MHz RF network, and the mechanism of date collision avoidance and retransmission. Owing to simplicity and practicality, this scheme is suitable for the application in family internal network.